SISTEM PENDUKUNG KEPUTUSAN PEMBERIAN KREDIT DENGAN MENGGUNAKAN METODE MFEP UNTUK MENGURANGIRESIKO KREDIT - Dadang Haryanto (LPPM STMIK DCI, 2017)
Decision-making is an activity that is important in today's modern business era. Basically the decision-making is a systematic approach to the nature of a problem, gathering facts - facts, determining which of the alternatives facing mature, and taking action according to the calculation is the most appropriate action. Decision-making is often faced with the complexity and scope of decision-making with so much data. For this purpos it is necessary to set a system that is able to solve problems efficiently and effectively, which was then called the Decision Support System.Decision support systems can be made using various calculation models of decision-making depends on decision-making object. Model of decision-making will lead to a decision maker in determining the appropriate model with the problem at hand. This paper consists of a model of decision-making that is Multi Factor Evaluation Process as a decisio making process involving many criteria. This paper describes the research design of a decision support system application using the loan to reduce the risk Mfep Process Keywords: Information Systems-Based Decision Support Computer, MFEP Analysis, Data Flow Diagram (DAD), Entity Relationship Diagram (ER-Diagram)New!Click the star to sav